FACTORS INFLUENCING THE ADOPTION OF ISO 14001 EMS BY ORGANIZATIONS IN SOUTH AFRICA - Puling, Leloko (My University, 2014)
Many organizations in South Africa have adopted the ISO 14001 Environmental Management System (EMS). The results of implementing this system are beneficial, when viewed from a corporate and environmental perspective. However, there is no evidence to suggest a corresponding overwhelming acceptance of the system by some organizations, despite the obvious benefits. It is against this background that the study aimed at identifying factors that influence the adoption of ISO 14001 EMS by organizations in South Africa. A qualitative multi-case study approach was used to address the research questions. Data was sourced from three organizations that have recently implemented the system. One of the outcomes of the study confirmed that while there are no direct legal requirements for an adoption of the system, it resulted in improved legal compliance. Another outstanding benefit was an improved corporate image amongst internal and external stakeholders. Despite these benefits, the adoption of the system was perceived to be costly. Organizations that adopted the system, established dedicated units to ensure its implementation. They also followed an open approach to understanding the needs of the system. Critical factors for the successful implementation of ISO 14001 EMS were the benefits to the overall system and an enhanced environmental performance. In addition, costs and the incorporation and implementation of the system into the organization’s strategic decisions played major roles in the decision to adopt this system. On the other hand, several factors that contributed to the non-adoption of the system were the following: resource constraints, delayed evidence of the impact of ISO 14001 EMS, lack of support from operational staff and management, as well as the limited focus on the establishment of environmental systems. Respondents also criticised the ISO 14001 EMS based on a combination of the preceding factors.
MM (P&DM)
Keywords: Environmental management standards